The effect of internal and external sources on product innovation: colombian context (2022)
Product innovation have been recognized as an important factor to firms' survival. To develop product innovations, companies require different knowledge sources. This research aims to identify the effects of both internal and external sources on product innovation. Using logistic regression, we test the proposed model using data from the Colombian Manufacturing Industry Technological Development and Innovation Survey (TDIS). The results suggest that internal, market and free access sources have a significant positive impact on the probability of companies developing product innovation.